Actual Problems of Theory and History of Art — 2018. From Antiquity to the Renaissance. Borders and Horizons - Kisbali, Tamás Péter; Nalimova, Nadezhda A.; Preobrazhenskij, Aleksandr S.; Pozhidaeva, Anna V.; Lopukhova, Marina A.; Guseva, Anna V.; Staniukovich-Denisova, Ekaterina Iu. (Actual Problems of Theory and History of Art, 2019)
This article presents the volume of collected papers that were delivered as reports at the “Actual Problems of History and Theory of Art VIII” International Conference held in Moscow in October, 2018. The book mainly contains the materials on art from ancient times till the Renaissance, Oriental studies and art critical surveys. Taking the main debating topic and the emphasis of the conference of 2018 into consideration, along with the idea of Borders and Horizons that was in the focus of the conference, the book is also focused on the problems of insight and interpretation of boundaries between genres, media, schools, styles, and epochs.